2021
DOI: 10.3390/cancers13215542
|View full text |Cite
|
Sign up to set email alerts
|

CCR4 as a Therapeutic Target for Cancer Immunotherapy

Abstract: CCR4 is a chemokine receptor mainly expressed by T cells. It is the receptor for two CC chemokine ligands, CCL17 and CCL22. Originally, the expression of CCR4 was described as highly selective for helper T type 2 (Th2) cells. Later, its expression was extended to other T cell subsets such as regulatory T (Treg) cells and Th17 cells. CCR4 has long been regarded as a potential therapeutic target for allergic diseases such as atopic dermatitis and bronchial asthma. Furthermore, the findings showing that CCR4 is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 249 publications
(379 reference statements)
0
43
0
Order By: Relevance
“…In this regard, mogamulizumab, an anti-CCR4 monoclonal antibody, was recently developed for the treatment of CCR4-expressing adult T-cell leukemia/lymphoma [ 93 ]. The mogamulizumab treatment was also shown to efficiently deplete CCR4-expressing Treg cells and to increase the number of tumor-specific CD8 + T cells in the blood of patients with adult T-cell leukemia/lymphoma [ 173 , 174 ]. It was further shown that a CCR4 antagonist CCR4-351 inhibited Treg cell recruitment into tumor tissues in mice bearing murine pancreatic and colon cancers, and augmented tumor-specific immune responses [ 63 ].…”
Section: Treg Cellmentioning
confidence: 99%
See 4 more Smart Citations
“…In this regard, mogamulizumab, an anti-CCR4 monoclonal antibody, was recently developed for the treatment of CCR4-expressing adult T-cell leukemia/lymphoma [ 93 ]. The mogamulizumab treatment was also shown to efficiently deplete CCR4-expressing Treg cells and to increase the number of tumor-specific CD8 + T cells in the blood of patients with adult T-cell leukemia/lymphoma [ 173 , 174 ]. It was further shown that a CCR4 antagonist CCR4-351 inhibited Treg cell recruitment into tumor tissues in mice bearing murine pancreatic and colon cancers, and augmented tumor-specific immune responses [ 63 ].…”
Section: Treg Cellmentioning
confidence: 99%
“…Although the chemokine superfamily have long been regarded as highly promising therapeutic targets for drug development, currently only three drugs are approved: Maraviroc, a small-molecule CCR5 antagonist for blocking infection by CCR5-tropic HIV-1; Plerixafor, a small-molecule CXCR4 antagonist for the mobilization of hematopoietic stem cells from the bone marrow for transplantation in patients with non-Hodgkin’s lymphoma and multiple myeloma; Mogamulizumab, a fully humanized and glyco-engineered monoclonal anti-CCR4 antibody for patients with aggressive/refractory adult T cell leukemia/lymphoma (ATLL) and cutaneous T cell lymphomas (CTCLs) [ 93 , 173 , 197 ]. However, the recent impressive therapeutic success of immune checkpoint inhibitors in cancer immunotherapy have opened the possibility of clinical application of drugs targeting chemokines and chemokine receptors as an adjunct therapeutic drug for cancer immunotherapy or chemotherapy.…”
Section: The Chemokine Superfamily As Therapeutic Targets In Cancer Immunotherapymentioning
confidence: 99%
See 3 more Smart Citations